RILEM TC: reinforcement of timber elements in existing structures - Tannert, Thomas (2013)
The paper reports on the activities of the RILEM technical committee “Reinforcement of Timber Elements in Existing Structures”. The main objective of the committee is to coordinate the efforts to improve the reinforcement practice of timber structural elements. Recent developments related to structural reinforcements can be grouped into three categories: (i) addition of new structural systems to support the existing structure; (ii) configuration of a composite system; and (iii) incorporation of elements to increase strength and stiffness. The paper specifically deals with research carried out at the Bern University of Applied Sciences Switzerland (BFH), the University of Minho Portugal (UniMinho), and the University of Trento Italy (UNITN). Research at BFH was devoted to improve the structural performance of rounded dovetail joints by means of different reinforcement methods: i) self-tapping screws, ii) adhesive layer, and iii) a combination of selftapping screws and adhesive layer. Research at UNITN targeted the use of “dry” connections for timber-to-timber composites, specifically reversible reinforcement techniques aimed at increasing the load-bearing capacity and the bending stiffness of existing timber floors. At UniMinho, double span continuous glulam slabs were strengthened with fibre-reinforced-polymers. All three examples demonstrate the improved structural performance of timber elements after reinforcing them.